Social science teachers’ perceptions and practices of global citizenship education: A case study of primary schools in Bangladesh - Rahman, Tanjima; Islam, Khairul; Rahman, Arifur (Journal of Interdisciplinary Studies in Education, 2025)
This study investigated social science teachers' perceptions of and practices in global citizenship education (GCED) through a case study of two government primary schools in Bangladesh. The study was qualitative to obtain in-depth insight from the participants. The schools and participants were selected purposively. In-depth interviews were conducted with four social science teachers and two head teachers. Two FGDs were conducted with students, and four classrooms were observed. The data were analyzed thematically, and nine themes emerged, such as knowledge of GCED; perceptions of diversity, empathy, and solidarity; GCED in the curriculum; pedagogies for GCED; cocurricular activities; GCED; student voice, engagement, and GCED; practicing GCED in the classroom and school; practicing equality in and out of the classroom; and ensuring critical pedagogy through student voice and engagement.